Leydig cell tumor: report of three cases - Pioner, Giovane (2022)
Leydig cell tumors are the most common tumors of the gonadal stroma. They account for 3% of all testicular tumors, but only 10% of cases are maligns. The authors report three cases of Leydig cell tumors of the testis observed in six years. All patients had radical orchiectomy by inguinal approach. Follow-up for 5 months to five years are done: none of the patients has died for the tumor and all are without signs of disease recurrence.